2014
DOI: 10.1371/journal.pone.0096582
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure and Molecular Variability of Cucumber mosaic virus Isolates in the United States

Abstract: Cucumber mosaic virus (CMV) has a worldwide distribution and the widest host range of any known plant virus. From 2000 to 2012, epidemics of CMV severely affected the production of snap bean (Phaseulos vulgaris L.) in the Midwest and Northeastern United States. Virus diversity leading to emergence of new strains is often considered a significant factor in virus epidemics. In addition to epidemics, new disease phenotypes arising from genetic exchanges or mutation can compromise effectiveness of plant disease ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 76 publications
10
43
0
9
Order By: Relevance
“…Th e virus diversity cannot be attributed to the eff ects of hosting as has been demonstrated in previous research from USA and China (Liu et al 2009;Nouri et al 2014). Our results also showed that host diff erences cannot be attributed to the genetic diversity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Th e virus diversity cannot be attributed to the eff ects of hosting as has been demonstrated in previous research from USA and China (Liu et al 2009;Nouri et al 2014). Our results also showed that host diff erences cannot be attributed to the genetic diversity.…”
Section: Discussionsupporting
confidence: 67%
“…Negative selection can reduce genetic variation in a population of viruses and increase the maintenance of coat protein stability. Negative selection of CMV coat protein abundance has been reported in previous studies (Liu et al 2009;Nouri et al 2014).…”
Section: Discussionmentioning
confidence: 83%
“…Ülkemizde biber, domates ve kavun bitkilerinde CMV enfeksiyonunun karakterizasyonu amacı ile gerçekleştirilen bir çalışmada CMV izolatlarının alt grup IA'ya ait olduğu bulunmuştur (Çağlar 2006). Her iki çalışmada Türkiye'de gerçekleştirilmesine rağmen, aynı bölge izolatlarının farklı alt gruplarda olabileceği bilinmektedir (Nouri et al 2014, Eyvazi et al 2015, Ohshima et al 2016. Salem et al (2010) Gerçekleştirilen bu çalışma ile Türkiye'de ilk kez CMV enfeksiyonu ticari olarak börülce yetiştiriciliği yapılan alanlarda doğal enfeksiyon olarak tespit edilmiştir.…”
Section: Benzerlik Filogenetik Ve Evrimsel Farklılık Analizleriunclassified
“…Las secuencias disponibles reportadas en GenBank para cmv aislado en banano americano tienen los siguientes números de accesión: AM055602.1, DQ640743.1, AM158321.1, DQ152254.1, U32858.1, U32859.1, M98501.1, M57602.1. Para alinear las secuencias se utilizó el programa BioEdit® (versión 5.0.9.1) y se buscaron secuencias de consenso de 18 a 25 pb (Nouri et al 2014). Para el diseño de cebadores se utilizó el programa Primer3 (versión 0.4.0) y se configuraron parámetros para descartar primers con alta formación de dímeros o con hibridaciones inespecíficas (Medrano et al 2006).…”
Section: Diseño De Primers De Detecciónunclassified
“…El ARN 1 y el ARN 2 codifican proteínas que intervienen en la replicación, además de codificar proteínas multifuncionales. El ARN 3 codifica las proteínas de la cápside y del movimiento (Nouri et al 2014). Los ARN subgenómicos (RNA 4 y RNA 4A) codifican para la CP (proteína de la cápside) y para la 2b (proteína supresora del silenciamiento génico) (Ding et al 1994;Jacquemond 2012).…”
Section: Introductionunclassified